2015
DOI: 10.1021/acs.analchem.5b02103
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection of Low-Abundance Host Cell Protein Impurities in High-Purity Monoclonal Antibodies Down to 1 ppm Using Ion Mobility Mass Spectrometry Coupled with Multidimensional Liquid Chromatography

Abstract: The enormous dynamic range of proteinaceous species present in protein biotherapeutics poses a significant challenge for current mass spectrometry (MS)-based methods to detect low-abundance HCP impurities. Previously, an HCP assay based on two-dimensional chromatographic separation (high pH/low pH) coupled to high-resolution quadrupole time-of-flight (QTOF) mass spectrometry and developed in the author's laboratory has been shown to achieve a detection limit of about 50 ppm (parts per milion) for the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 34 publications
1
87
1
1
Order By: Relevance
“…The workflow developed in this study was based on a fast (1-hour) and robust LC-MS /MS method that used charge-surface hybrid (CSH) 7,24 C18 UHPLC interfaced with a mass spectrometer with fast scanning speed (MS/MS at 20Hz). The average relative standard deviation for retention time of 5 different peptides from 5 LC-MS analyses collected over 2 months was 1.1%, indicating good reproducibility of the LC separation.…”
Section: Sensitivity and Robustness Of The 1d Uhplc-ms/ms Using Data-mentioning
confidence: 99%
See 2 more Smart Citations
“…The workflow developed in this study was based on a fast (1-hour) and robust LC-MS /MS method that used charge-surface hybrid (CSH) 7,24 C18 UHPLC interfaced with a mass spectrometer with fast scanning speed (MS/MS at 20Hz). The average relative standard deviation for retention time of 5 different peptides from 5 LC-MS analyses collected over 2 months was 1.1%, indicating good reproducibility of the LC separation.…”
Section: Sensitivity and Robustness Of The 1d Uhplc-ms/ms Using Data-mentioning
confidence: 99%
“…To address these challenges, methods using advanced liquid chromatography (LC) and mass spectrometry (MS) techniques have been developed, most of which focus on detecting low level HCPs in the final monoclonal antibody (mAb) products. [6][7][8][9][10][11] However, there is currently an unmet need to provide high throughput and robust LC-MS/MS analysis of HCPs in various in-process pools to help design and optimize purification processes toward optimal clearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of an effort to help users understand the conditions under which 2D-LC provides more resolving power than 1D-LC separations for peptide analyses, the Heinisch group recently demonstrated that the peak capacity of 2D-LC separations is superior to that of 1D-LC separations for analysis times longer than about five minutes [18]. In the area of Host Cell Protein (HCP) analysis, Donenau and coworkers have demonstrated the use of heartcutting 2D-LC [19,20] and offline comprehensive 2D-LC [21] to detect trace-level peptide markers of HCPs. This is very important to quality assurance for biotherapeutic mAbs.…”
Section: Peptide Level Analysismentioning
confidence: 99%
“…Efforts have been made in characterizing protein profile of biological samples such as placenta [17], urine [18] plants [19], etc. The techniques applied to this goal are diverse and include protein depletion and mass spectrometry [17,20], improved fractionation and purification methods [18], high-resolution NMR [21] among others.…”
Section: Introductionmentioning
confidence: 99%